The Poetry of Politics. (May 2013) - Joffe, Carole
Katha Pollitt, longtime columnist for The Nation and one of the country's leading political commentators, was recently interviewed by sociologist Carole Joffe. The interview offers Pollitt's views on such subjects as the state of the feminist movement, academic feminism, the 2012 elections, and sociology.